193k views
3 votes
X^y=p

Express in logarithmic form for the base.

X^y=p Express in logarithmic form for the base.-example-1

1 Answer

4 votes

ANSWER


y= log_(x)(p)

Step-by-step explanation

The given expression is


{x}^(y) = p

We take logarithm of both sides to base x.


log_(x)( {x}^(y) ) = log_(x)(p)

Apply the power rule of logarithms to get:


ylog_(x)( {x}) = log_(x)(p)

Logarithm of the base is 1.

This implies that,


y( 1) = log_(x)(p)


y= log_(x)(p)

User Cnaegle
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.